Determinants of private investments in Turkey: Examining the role of democracy - Selçuk Akçay; Alper Karasoy (Review of Economic Perspectives, 2020)
This study investigates the determinants of private sector investments in Turkey with a focus on democracy. Using the Autoregressive Distributed Lag (ARDL) bounds testing approach and two different democracy indices along with the other determinants of private investment, we estimated a private investment function for the 1975-2014 period. Our main finding is that democracy has a profound positive impact on private investment. Moreover, the results show that: (i) public investment is a substitute to private investment; (ii) macroeconomic instability dissuades private investment; (iii) real interest is a serious impediment to private investment; (iv) financial development and GDP growth rate stimulate private investment.
Keywords: C32; E22; 330; ARDL; democracy; private investment; Turkey